Illness Identity: A Novel Predictor for Healthcare Use in Adults With Congenital Heart Disease. Issue 11 (21 September 0207) - Van Bulck, Liesbet; Goossens, Eva; Luyckx, Koen; Oris, Leen; Apers, Silke; Moons, Philip
Abstract : Background: To optimize healthcare use of adults with congenital heart disease, all important predictors of healthcare utilization should be identified. Clinical and psychological characteristics (eg, age and depression) have been found to be associated with healthcare use. However, the concept of illness identity, which assesses the degree to which congenital heart disease is integrated into one's identity, has not yet been investigated in association with healthcare use. Hence, the purpose of the study is to examine the predictive value of illness identity for healthcare use. Methods and Results: In this ambispective analytical observational cohort study, 216 adults with congenital heart disease were included. The self‐reported Illness Identity Questionnaire was used to assess illness identity states: engulfment, rejection, acceptance, and enrichment. After 1 year, self‐reported healthcare use for congenital heart disease or other reasons over the past 6 months was assessed including hospitalizations; visits to general practitioner; visits to medical specialists; and emergency room visits. Binary logistic and negative binomial regression analyses were conducted, adjusting for age, sex, disease complexity, and depressive and anxious symptoms. The more profoundly the heart defect dominated one's identity (ie, engulfment), the more likely this person was to be hospitalized (odds ratio=3.76; 95% confidence interval=1.43–9.86), to visit a medical specialist (odds ratio=2.32; 95% confidence interval=1.35–4.00) or a general practitioner (odds ratio=1.78; 95% confidence interval=1.01–3.17), because of their heart defect. Conclusions: Illness identity, more specifically engulfment, has a unique predictive value for the occurrence of healthcare encounters. This association deserves further investigation, in which the directionality of effects and the contribution of illness identity in terms of preventing inappropriate healthcare use should be determined.